Consumers’ Perceptions of E-Service Quality on Online Shopping in the Nepalese Metropolitan Cities (Pravaha, 2024)
This paper attempts to examine the consumers’ perceptions of e-service quality on online shopping in six metropolitan cities of Nepal. Descriptive and causal-comparative research design have used in this study. Data are collected from 525 respondents by using a questionnaire survey where 600 questionnaires (100 respondents from each metropolitan city) were distributed. Consumer satisfaction and purchase intention are the dependent variables. Similarly, website design, trust, reliability, responsiveness, and personalization are the independent variables. Descriptive statistics, correlation analysis and multiple regression models are used to analyse the data. It is observed that all independent variables have a positive and significant impact on consumer satisfaction and purchase intention. This study helps marketers to understand factors influencing consumer purchase intention on online shopping. The study is very relevant because it can give a clear picture of the future of online markets in Nepal and the emerging trends in this particular field. It is expected that this paper may contribute to fill an important gap in the literature and may add some values to the existing literature.